AYAT-AYAT AL-QUR’AN SEBAGAI LANDASAN ETIS GOTONG ROYONG: KAJIAN TAFSIR SOSIAL - Wahyu Saputra; Edi Hermanto (PT. Sulthan Journal Publisher, 2025)
Mutual cooperation (gotong royong) is a fundamental social value deeply rooted in Indonesian culture and holds strong relevance within Islamic teachings. The Qur’an functions not only as guidance for ritual worship but also as a source of social ethics that emphasizes cooperation, solidarity, and collective responsibility. This study aims to analyze the concept of mutual cooperation from the Qur’anic perspective and examine its relevance to contemporary Indonesian social life. This research employs a qualitative method using library research and a social exegesis (tafsīr ijtimā‘ī) approach. The data are analyzed through selected Qur’anic verses related to mutual assistance, such as Q.S. Al-Mā’idah [5]: 2 and Q.S. Āli ‘Imrān [3]: 112, supported by interpretations from classical and modern Muslim scholars. The findings indicate that mutual cooperation in the Qur’anic framework represents an expression of faith and social worship, requiring a balance between the relationship with God (ḥabl min Allāh) and relationships among human beings (ḥabl min al-nās). The Prophet Muhammad’s practices, including collective efforts in social and community development, highlight the importance of solidarity in building a just and civilized society. This study concludes that Qur’an-based values of mutual cooperation remain relevant as an ethical foundation for addressing modern challenges such as individualism and declining social awareness.